Molecular Determinants of Ca(V)2.1 Channel Regulation by Calcium-binding Protein-1 - Few, Alexandra P. (American Society for Biochemistry and Molecular Biology, 2011)
Presynaptic Ca(V)2.1 channels, which conduct P/Q-type Ca(2+) currents, initiate synaptic transmission at most synapses in the central nervous system. Regulation of Ca(V)2.1 channels by CaM contributes significantly to short term facilitation and rapid depression of synaptic transmission. Short term synaptic plasticity is diverse in form and function at different synapses, yet CaM is ubiquitously expressed. Differential regulation of Ca(V)2.1 channels by CaM-like Ca(2+) sensor (CaS) proteins differentially affects short term synaptic facilitation and rapid synaptic depression in transfected sympathetic neuron synapses. Here, we define the molecular determinants for differential regulation of Ca(V)2.1 channels by the CaS protein calcium-binding protein-1 (CaBP1) by analysis of chimeras in which the unique structural domains of CaBP1 are inserted into CaM. Our results show that the N-terminal domain, including its myristoylation site, and the second EF-hand, which is inactive in Ca(2+) binding, are the key molecular determinants of differential regulation of Ca(V)2.1 channels by CaBP1. These findings give insight into the molecular code by which CaS proteins differentially regulate Ca(V)2.1 channel function and provide diversity of form and function of short term synaptic plasticity.